STRATEGI KAMPANYE PARTAI KEADILAN SEJAHTERA (PKS) PILEG 2014 DI KABUPATEN BOYOLALI - Yoga Ade Perdana; Kushandajani .; Nunik Retno H (Journal of Politic and Government Studies, 2014)
PARTAI KEADILAN SEJAHTERA (PKS) CAMPAIGN STRATEGY IN 2014LEGISLATIVE ELECTION IN BOYOLALIElection is a phenomenon that always happens in a democracy. In the elections, thepolitical parties need a plan that is prepared in an effort to win the competition with the otherparticipants and gained the most votes in the election. An accurate planning is a key requirementfor the success of political parties in achieving the goals set.The formulation problem in this research is: “How Strategy Campaign of Partai KeadilanSejahtera (PKS) Legislative Election 2014 in Boyolali?”Meanwhile, the purpose of this researchis to provide an overview of Partai Keadilan Sejahtera (PKS) legislative election strategy 2014 inBoyolali.The method of this research used qualitative, with the Chairman of DPD PKS Boyolali,General Secretary DPD PKS Boyolali, Chairman of the PKS Success Team in Boyolali, DPDPKS members in Boyolali, and DPRD PKS Council Staff in Boyolali as informants of thisresearch. While interviews and documentation used to collect the data, with the analysis ofqualitative data through the stages of data reduction, data display and conclusion.The results of this research indicate that the strategy of PKS legislative election in the2014 in Boyolali applying political strategy with political marketing approach of segmentation byselecting a particular group of people that are most likely to be influences by PKS campaignstrategy program (mapping the voters); Targeting by targeting a particular group of constituentswho are expected to achieved their voice easily; Positioning which is the strategy to instill acertain image to one or several groups of voters. In the campaign strategy, PKS has 2 campaignsconducted in Boyolali by using Media and Direct Selling.Based on the results of the election in 2014, PKS only achieved 36.042 votes or equal to 4DPRD parliament chairs and in the 2009 election PKS also only get 4 DPRD parliament chairs inBoyolali, it means the strategy that is adopted assessed stagnant. The political strategy of PKS inBoyolali is classified into a failed campaign. However, PKS should still have repaired thestrategies to face the next election.Keywords: Election, PKS, Strategy